Cultural legacies and political preferences: the failure of separatism in the Swiss Jura. Issue 2 (21st December 2015) - Siroky, David S.; Mueller, Sean; Hechter, Michael
Abstract : The study of secession generally stresses the causal influence of cultural identities, political preferences, or ecological factors. Whereas these different views are often considered to be mutually exclusive, this paper proposes a two-stage model in which they are complementary. We posit that cultural identities matter for explaining secessionism, but not because of primordial attachments. Rather, religious and linguistic groups matter because their members are imbued with cultural legacies that lead to distinct political preferences – in this case preferences over welfare statism. Further, ecological constraints such as geography and topography affect social interaction with like-minded individuals. On the basis of both these political preferences and ecological constraints, individuals then make rational choices about the desirability of secession. Instrumental considerations are therefore crucial in explaining the decision to secede, but not in a conventional pocketbook manner. To examine this theory, we analyze the 2013 referendum on the secession of the Jura Bernois region from the Canton of Berne in Switzerland, using municipal level census and referendum data. The results lend support to the theory and suggest one way in which the politics of identity, based on factors like language and religion, can be fused with the politics of interest (preferences for more or less state intervention into the polity and economy) to better understand group behavior.